Remembraces of the centenary of independece of Central America 1921 - Lemus Rivas, Marvin Nahum (2019)
In preambles of the bicentenary of political independence of Honduras from Spain celebration, various issues related to such juncture and the centenary of it, recover interest, so the question arises, what were the eventualities that occurred in the celebration of the centenary of independence and what are the perspectives towards the bicentennial in 2021? This article analyzes the political, social and cultural manifestations made in the Centennial of Independence in Tegucigalpa, from a historical perspective, combining them with the present civic celebrations of September, also exposing the change of positions and of interest among the countries of the Central American isthmus for 2021, all based on content analysis.